Genome-Wide Association Study of Resistance to Soybean Cyst Nematode (Heterodera glycines) HG Type 2.5.7 in Wild Soybean (Glycine soja) - Zhang, Hengyou; Li, Chunying; Davis, Eric L.; Wang, Jinshe; Griffin, Joshua D.; Kofsky, Janice; Song, Bao-Hua (Frontiers in Plant Science, 2016)
Soybean cyst nematode (SCN) is the most destructive soybean pest worldwide. Host plant resistance is the most environmentally friendly and cost-effective way of mitigating SCN damage to soybeans. However, overuse of the resistant soybean (Glycine max (L.) Merr.) cultivars from limited genetic resources has resulted in SCN race shifts in many soybean-growing areas. Thus, exploration of novel sources of SCN resistance and dissection of the genetic basis are urgently needed. In this study, we screened 235 wild soybean (Glycine soja Sieb. & Zucc.) accessions to identify genotypes resistant to SCN HG Type 2.5.7 (race 5), a less investigated type but is prevalent in the southeastern US. We also dissected the genetic basis of SCN resistance using a genome-wide association study with SNPs genotyped by SoySNP50k iSelect BeadChip. In total, 43 resistant accessions (female index < 30) were identified, with ten SNPs being significantly associated with SCN HG 2.5.7 resistance in this wild species. Furthermore, four significant SNPs were localized to linked regions of the known quantitative trait locus (QTL) rhg1 on chromosome 18. The other four SNPs on chromosome 18 and two SNPs on chromosome 19 are novel. Genes encoding disease resistance-related proteins with a leucine-rich region, a mitogen-activated protein kinase (MAPK) on chromosome 18, and a MYB transcription factor on chromosome 19 were identified as promising candidate genes. The identified SNPs and candidate genes will benefit future marker-assisted breeding and dissection of the molecular mechanisms underlying the soybean-SCN interaction.